Design of ACS712-based Current Sensing Monitoring Evaluation for PWM Solar Charge Controller - Wibowo, Apriansyah; Jayendra, I Gede Bagus; Utari, Dhea Yunita; Rasyiid, Muhammad; Aprilianto, Rizky Ajie (Sainteknol : Jurnal Sains dan Teknologi, 2024)
The rise of renewable energy has led to growing interest among researchers in optimizing renewable energy systems to harvest the highest possible energy output, especially in photovoltaic (PV) systems. Photovoltaic systems generate energy from sunlight, but the intermittent nature of sunlight poses a challenge for providing constant power. Another problem is that the most affordable conventional Pulse-Width Modulation (PWM) controllers on the market are unable to provide a current monitoring system. This issue is critical when users require detailed data to perform diagnostics on their PV systems. In this study, a monitoring system using microcontrollers and the ACS712 current sensor was developed and implemented to observe the behavior and performance of a photovoltaic (PV) charging system based on the current output from a PWM controller. The primary objective of this system is to develop a solution that can identify PV modules operating under suboptimal conditions, which can be caused by various factors such as increased solar cell temperature, cloud cover effects, PV module degradation, and the performance of the Pulse-Width Modulation (PWM) solar charge controller (SCC). This is crucial because PV modules can be susceptible to various environmental and technical factors that may impact their efficiency and power output. By closely monitoring the performance of each PV module using the ACS712-based current sensing system, the researchers aim to promptly detect and address any issues that may arise, ensuring the overall optimal operation of the PV system.